2022
DOI: 10.1136/ijgc-2022-003764
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin plus pegylated liposomal doxorubicin in patients with disease progression after PARP inhibitor maintenance: a real-life case–control study

Abstract: ObjectivePoly (ADP-ribose) polymerase (PARP) inhibitor resistance is problematic in epithelial ovarian cancer management and sequencing strategies may be performed to overcome this issue. In this context, our study evaluated the role of non-platinum doublet pegylated liposomal doxorubicin/trabectedin in ovarian cancer platinum-sensitive patients who experienced disease progression under PARP inhibitor maintenance.MethodsThis case–control study includes patients with recurrent epithelial ovarian cancer treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Interestingly, previous data have shown that PLD + Trabectedin after PARP inhibitors achieves similar oncological outcomes compared with a platinum-based regimen [ 28 ]. Therefore, in a sequence strategy, PLD + Trabectedin still remains a reasonable choice following PARP inhibitors progression, sparing platinum compound for subsequent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous data have shown that PLD + Trabectedin after PARP inhibitors achieves similar oncological outcomes compared with a platinum-based regimen [ 28 ]. Therefore, in a sequence strategy, PLD + Trabectedin still remains a reasonable choice following PARP inhibitors progression, sparing platinum compound for subsequent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that a combination of trabectedin/PLD might be as effective as a platinum-based, both in terms of PFS and OS, with acceptable toxicity profiles on both sides. 50 …”
Section: What Is the Role Of Trabectedin In The Current Clinical Prac...mentioning
confidence: 99%
“…The MITO-8 trial demonstrated that treating patients with a platinum-free interval of 6–12 months with a non-platinum-based regimen before re-introducing platinum did not improve survival,35 but this scenario could change in the post-introduction of PARPi era. Moreover, the pegylated liposomal doxorubicin–trabectedin doublet should be further evaluated in the subgroup of patients with a platinum-free interval of 6–12 months as the results from the INOVATYON trial could be reversed after the advent of PARPi in the first-line setting 36 37. At least theoretically, not only non-platinum agents could be more effective than expected as second-line treatment in patients who progress after PARPi, but the interposition of non-platinum-based chemotherapy may help overcome cross-resistance and possibly improve the response to subsequent platinum-based therapy.…”
Section: What Are the Treatment Strategies In Platinum-eligible Patie...mentioning
confidence: 99%